IDENTIFIKASI MOLEKULER DAN STATUS KONSERVASI IKAN PARI HIU (RHINIDAE) YANG DIDARATKAN DI PULAU BANGKA - Siti Aisyah; Arthur Muhammad Farhaby (JFMR (Journal of Fisheries and Marine Research), 2021)
The high activity of catching Shark Ray (Rhinidae) have a big impact on the population and affect the balance of the marine ecosystem. This is supported by the characteristics of stingrays that have a lower reproductive ability, slower growth and higher risk of death. Lack of database information, relating to the Shark Ray can reduce oversight or regulations governing the production of the total catch. So the condition is feared impact on the survival of Shark Ray, especially in Bangka Belitung. One of the important databases that must be done is the accurate identification of fish species Shark Ray as a reference in determining the conservation status. The purpose of this research is to identify the molecular basis Shark Ray and the conservation status of the Shark Ray landed on Bangka Island. Shark Ray samples obtained from a source of potential landing in Bangka Island, namely PPN Sungailiat (Bangka Regency), TPI Ketapang (Pangkalpinang City) and TPI Kurau (Central Bangka Regency). The research method consists of three stages: collection of samples, the molecular identification (mtDNA Cytochrome Oxidase Subunit 1 / COI gene), phylogenetic analysis and conservation status of Shark Ray. The results of the COI gene nucleotide character matching were performed by using the BLAST program integrated into GenBank pages and showed that the three samples of Shark Rays were identified as Rhina Ancylostoma species (Bowmouth guitarfish, Shark Ray) with a rate of similarity of 100%. Based on data from the IUCN Red List, the species Rhina Ancylostomain the category of Critically Endangered (CR) and based on the status of trade, at the 18th CoP meeting in Geneva, on August 2019, CITES has added Wedgefishes (Family Rhinidae) in Appendix II.